2021
DOI: 10.1016/j.jtbi.2021.110838
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative success in epithelial public goods games

Abstract: Cancer cells obtain mutations which rely on the production of diffusible growth factors to confer a fitness benefit. These mutations can be considered cooperative, and studied as public goods games within the framework of evolutionary game theory. The population structure, benefit function and update rule all influence the evolutionary success of cooperators. We model the evolution of cooperation in epithelial cells using the Voronoi tessellation model. Unlike traditional evolutionary graph theory, this allows… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…To better understand the success of cooperation on realistic simple epithelia, Renton & Page studied both the Prisoner’s Dilemma [124] and sigmoid-benefit public goods games [125] on Voronoi tessellations. They found that the crucial mechanism required for cooperation to succeed was the spatial decoupling of birth and death, with nuclei moving under the forces created by cells vanishing and appearing anywhere in the population.…”
Section: The Role Of Spacementioning
confidence: 99%
“…To better understand the success of cooperation on realistic simple epithelia, Renton & Page studied both the Prisoner’s Dilemma [124] and sigmoid-benefit public goods games [125] on Voronoi tessellations. They found that the crucial mechanism required for cooperation to succeed was the spatial decoupling of birth and death, with nuclei moving under the forces created by cells vanishing and appearing anywhere in the population.…”
Section: The Role Of Spacementioning
confidence: 99%
“…This mathematical tool has also been applied to analyze biological problems, and lately to explore the complexity of cancer. The hawk-dove game 19 , the prisoner’s dilemma 20 , coordination games 21 , and multiplayer public good games such as the volunteer’s dilemma 22 , for example, are different theoretical scenarios that have been applied to cancer analysis in recent years.…”
Section: Gamesmentioning
confidence: 99%